Violence in the Household (KDRT) Perspective Maqashid Sharia (Case Study at Sungguminasa District Court) - Putri Zaidhatul, Fania; Kurniati, Kurniati; Asni, Asni (Pascasarjana UIN Alauddin Makassar, 2023)
This Study discuss about violence in Household (domestic violence) in perspective maqashid sharia. This study employed a field research design utilizing qualitative and descriptive research methods as well as normative theology and juridical approach. The data sources in this research are primary data, secondary data and tertiary data. The result of this research show that : 1) Numerous causes, including communication, someone's character or behavior, jealousy, money, being married young, having the wrong idea about religion, emotions, and competition, are causative elements of violence in households. Putting this in perspective Maqashid Sharia has a significant impact on upholding someone's property, religion, soul, mind, and children because these are factors that can lead to further domestic violence; 2) Settlement efforts to resolve domestic violence are carried out by following the criminal procedural law system as regulated in Law Number 8 of 1981, concerning Criminal Procedure Law (KUHAP) and in imposing sentences based on Law No. 24 of 2004 concerning the Elimination of Domestic Violence (UU PKDRT), in this case the resolution efforts carried out by the Sungguminasa District Court are in line with the objectives of Islamic law, namely the protection of ensuring the 5 main principles in Islam, preserving religion, soul, mind, lineage and property.